Biomechanics feedback to Olympic athletes - two feedback models - Baker, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
One of the challenges for biomechanics, as a discipline in general, has been to provide meaningful and timely feedback to athletes. This is particularly the case where the biomechanist is working with athletes frequently over a period of time. A number of different approaches in providing feedback to athletes can be made depending upon the question asked, testing setting, and the data collected. These issues need to be balanced when dealing with Olympic athletes.